ASPECTS OF LEGAL PROTECTION FOR CONSUMERS’ ONLINE BUSINESS - Nurul Eka Oktaviani (President University, 2015)
There are some Laws that regulated the legal protection for consumer of online business, there are Law of Consumer Protection no. 8 Year 1999, Law of Electronic Information and Transaction No. 11 Year 2008 and Government Regulation of Operation System and Electronic Transaction No. 82 Year 2012 abds action listed in that law is already clearly stated. To arrest the online business fraud perpetrators is not only because of the loss of material, a material can be searched for later in another day. The most important thing is the existence of a regretful feeling caused by an arrest to the perpetrators of online business fraud. Then hopefully there will be no more online business fraud because the perpetrators afraid of the sanction in the Law. Besides that, the victim will get the sense of satisfaction when the police managed to find a person who cheated him. Although if the case is complete and ready to be relegated to the prosecutor and transferred to the district court, in criminal case, there would be no compensation obtained by the victim unless the victim reported the perpetrators in the form of civil violation.